Gender Trends in Dermatology Research: Shifting Authorship Landscape in Indian Journals - Mediboina, Anjali; Bhupathi, Meghana; Janapareddy, Keerthana (International Journal of Medical Students, 2024)
Background: Historically, research authorship has been male dominated, particularly in dermatology. Gender equity in medical research is vital for diverse perspectives and rigorous science. In India, gender trends in dermatology research among first authors remain understudied, limiting our understanding of gender inequalities in the field. Methods: This study analyzed Original Articles, Review Articles, and Case Reports in three prominent Indian Dermatology journals from January 2017 to May 2023. The first authors' genders were determined using Namsor V.2, cross-verified with social media profiles, and authors with undetermined genders were excluded. The authors' countries were identified based on their affiliated institutions. The data was analyzed using Microsoft Excel, with a predictive analysis using the FORECAST function. Results: Among 1,600 authors, 840 were female and 760 male. Male authors outnumbered female authors only in 2017. Female authors surpassed male authors in original articles and case reports, while fewer appeared in review articles. Predictive analysis revealed an increasing trend in female authors from 2023 to 2028, indicating evolving gender dynamics in dermatology research. Conclusion: While the rise in female representation in medical research is promising, concerns arise when fields become predominantly female, raising questions about their perceived value. Gender disparities in compensation further underscore these concerns, as male dermatologists earn more. Addressing such disparities is crucial and recognizing these issues and actively pursuing gender equality is essential for a more inclusive and equitable future in medicine.